A rare case of impacted supernumerary premolar causing resorption of mandibular first molar - R V Murali; K Gnanashanmugam; L Rajasekar; B S Kularashmi; B Saravanan (Wolters Kluwer Medknow Publications, 2015)
The management of patients with pain in today's general practice has become a major concern and sometimes this pain is related to some rare causes. A male patient aged 26 years reported with pain in the lower left molar region (36) and then an intra-oral periapical radiograph (IOPA), and orthopantomograph was taken. IOPA revealed the presence of supernumerary premolar causing pressure and root resorption of 36. Also, there was missing 21 and proximal decay in 11. Eleven was treated endodontically, and then bridge was done in relation to 11, 21 and 22. Lower anterior crowding was also present. The treatment plan was to extract 36 followed by orthodontic extrusion of the supernumerary premolar and also the correction of lower anterior crowding. Hidden approach (lingual orthodontics) was used as the patient was insisting upon the braces not being seen outside during the course of the treatment. Later all ceramic bridge was done in relation to 11, 21 and 22. Orthodontic tooth extrusion techniques offer excellent treatment options for Partially Impacted tooth. It is a well-documented clinical method for extruding sound tooth material from within the alveolar socket by light forces. The use of lingual technique for forced eruption enhance acceptance of orthodontic treatment by adults. The treatment of a young adult patient illustrates the importance of treatment planning from one discipline to another, communication among team members and the benefits of working together in an interdisciplinary approach